The first coleoid cephalopods from the Upper Cenomanian of Sicily (Italy) and their implications for the systematic-phylogenetic position of the Palaeololiginidae (Teudopseina). (3rd June 2017) - Fuchs, Dirk; Reitano, Agatino; Insacco, Gianni; Iba, Yasuhiro
Abstract : Our knowledge about the evolutionary history of coleoid cephalopods is mainly based on a few evolutionary windows. In particular, palaeogeographical data is strongly limited; every new fossil locality yielding coleoid remains is therefore of exceptional interest. Here, we describe the first coleoids from the Upper Cenomanian of Sicily (southern Italy). The material includes two fragmentary gladii, identified as Marekites nebrodensis sp. nov. and Rachiteuthis ? sp. These two related taxa from the north-western Mediterranean region differ from most of their contemporaries in the south-eastern Mediterranean Lebanon fauna. Owing to their lanceolate posterior gladius, both taxa are classified as members of the Palaeololiginidae, a previously poorly defined family of Mesozoic gladius-bearing octobrachians. In the light of our observations, the family can now be characterized by its very gently arcuate hyperbolar zone, as well as the occurrence of a constriction of the median field. Marekites nebrodensis sp. nov. confirms that Cretaceous palaeololiginids share a relatively longer free (rachis-like) median field than their Jurassic forerunner Palaeololigo . Besides systematic-morphological implications, the higher level phylogenetic position of Paleololiginidae is discussed. In this context, we reject the idea of Palaeololiginidae as early bathyteuthoid decabrachians. http://zoobank.org/urn:lsid:zoobank.org:pub:075B36B1-2ECF-406F-AD99-79C98B06C271